2016
DOI: 10.1016/j.numecd.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Higher protein intake is associated with increased risk for incident end-stage renal disease among blacks with diabetes in the Southern Community Cohort Study

Abstract: Background and Aims Diabetes, a risk factor for end-stage renal disease (ESRD), is associated with impaired protein metabolism. We investigated whether protein intake is associated with ESRD and whether the risk is higher among blacks with diabetes. Methods and Results We conducted a nested case-control study of ESRD within the Southern Community Cohort Study, a prospective study of low-income blacks and whites in the southeastern US (2002-2009). Through 2012, 1,057 incident ESRD cases were identified by lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…Our finding can be explaned by hyperfiltration that caused by HP leading to subsequent renal damage, as postulated by Brenner et al, [47] [54]. It may also be possible that by-products of excess protein metabolism could cause injury to podocytes and other kidney cells resulting in impaired kidney function and subsequent ESRD [53].…”
Section: Discussionsupporting
confidence: 62%
“…Our finding can be explaned by hyperfiltration that caused by HP leading to subsequent renal damage, as postulated by Brenner et al, [47] [54]. It may also be possible that by-products of excess protein metabolism could cause injury to podocytes and other kidney cells resulting in impaired kidney function and subsequent ESRD [53].…”
Section: Discussionsupporting
confidence: 62%
“…High dietary protein intake is thought to increase the nitrogen load, glomerular filtration rate, and renal hypertrophy 33. Malhotra et al also proved that increased dietary protein was associated with the incidence of end-stage kidney disease in patients with diabetes 34. This study also demonstrated that patients with diabetes with excessive dietary protein may increase the 8.9% incidence of eGFR decline, ≥40%, but this finding was not statistically significant (OR 1.089, 95% CI 0.716 to 1.656, p=0.690).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 86% of participants were enrolled at participating community health centers (CHC), institutions which provide primary health and preventive services in medically underserved areas [10]. A detailed description of SCCS methods is available on the study website (http://www.southerncommunitystudy.org/) and in previous publications [9, 1113]. SCCS participants provided written informed consent, and protocols were approved by the Institutional Review Boards of Vanderbilt University Medical Center and Meharry Medical College.…”
Section: Methodsmentioning
confidence: 99%